THE MEDIATING ROLE OF GOOD CORPORATE GOVERNANCE BETWEEN INTELLECTUAL CAPITAL AND FINANCIAL SUSTAINABILITY IN BALI LPDS - Ni Made Wanda Diajeng Sujana1; I Putu Mega Juli Semara Putra; I Nyoman Kusuma Adnyana Mahaputra (RADJA PUBLIKA, 2026)
Financial sustainability is crucial for ensuring the long-term viability of Village Credit Institutions (LPDs) in Bali. Although intellectual capital is recognized as a strategic organizational resource, empirical findings regarding its influence on financial sustainability remain inconclusive. Furthermore, studies examining the mediating role of good corporate governance in the relationship between intellectual capital and financial sustainability, particularly in community-based financial institutions, remain limited. This study aims to analyze the role of good corporate governance in mediating the influence of intellectual capital dimensions (human capital, social capital, and relational capital) on financial sustainability in LPDs in Bali Province. This study employed a quantitative approach using primary data collected through questionnaires distributed to LPD managers and employees. A total of 188 valid responses were analyzed using PLS-SEM with SmartPLS software. The results reveal that social capital and relational capital enhance good corporate governance, which subsequently improves financial sustainability. Good corporate governance mediates the relationship between intellectual capital dimensions and financial sustainability, except for human capital, which has no significant effect. These findings contribute to the intellectual capital and governance literature by demonstrating the role of governance quality in transforming social and relational capital into sustainable financial outcomes. The study also provides practical implications for strengthening governance practices and enhancing the long-term sustainability of LPDs.